Sea turtles to sidewinders : a guide to the most fascinating reptiles & amphibians of the west - Hood, Charles, 1959- (Timber Press, 2021)
"This accessible book encourages people to discover the amazing world of snakes, frogs, lizards, turtles, and newts. Emphasis is on "wow" species (colorful, fun), common backyard or easily-seen-on-a-day-hike species, and those species whose stories best reveal the changing face of nature today. All species accounts will have at least two photos, and a few have as many as five. Each entry will begin with a box of essential information to help orient the reader. An introductory chapter will define essential terms; talk about general natural history; discuss natives vs. exotics; provide pointers for viewing reptiles and amphibians; discuss safety (viz., how not to be bitten by snakes); and suggest citizen science projects. Timber's regional field guides have been quite successful; this book will provide more accessible-and interesting-information than a standard-format field guide, while still retaining the appeal of focusing on two fascinating groups of animals"--